Anodic Oxidation of Conductive Carbon and Ethylene Carbonate in High-Voltage Li-Ion Batteries Quantified by On-Line Electrochemical Mass Spectrometry. Issue 7 (25th March 2015) - Metzger, Michael; Marino, Cyril; Sicklinger, Johannes; Haering, Dominik; Gasteiger, Hubert A.
Abstract : The anodic oxidation stability of battery components like the conductive carbon black (Super C65) and the co-solvent ethylene carbonate (EC) is of great relevance, especially with regards to high-voltage cathode materials. In this study, we use On-line Electrochemical Mass Spectrometry (OEMS) to deconvolute the CO and CO2 evolution from the anodic oxidation of carbon and electrolyte by using a fully 13 C-isotope labeled electrolyte based on ethylene carbonate with 2 M LiClO4 . We present a newly developed two-compartment cell, which provides a tight seal between anode and cathode compartment via a solid Li + -ion conducting separator, and which thus allows us to examine the effect of trace amounts of water on the anodic oxidation of carbon ( 12 C) and ethylene carbonate ( 13 C) at high potentials (> 4.5 V) and 10 to 60°C. Moreover, we report on the temperature dependence of the water-driven hydrolysis of ethylene carbonate accompanied by CO2 evolution. Finally, by quantifying the evolution rates of 12 CO/ 12 CO2 and 13 CO/ 13 CO2 at 5.0 V, we demonstrate that the anodic oxidation of carbon and electrolyte can be substantial, especially at high temperature and in the presence of trace water, posing significant challenges for the implementation of 5 V cathode materials.